Insights from 20 years of the Molecule of the Month. Issue 4 (17th June 2020) - Goodsell, David S.; Zardecki, Christine; Berman, Helen M.; Burley, Stephen K.
Abstract: For 20 years, Molecule of the Month articles have highlighted the functional stories of 3D structures found in the Protein Data Bank (PDB). The PDB is the primary archive of atomic structures of biological molecules, currently providing open access to more than 150, 000 structures studied by researchers around the world. The wealth of knowledge embodied in this resource is remarkable, with structures that allow exploration of nearly any biomolecular topic, including the basic science of genetic mechanisms, mechanisms of photosynthesis and bioenergetics, and central biomedical topics like cancer therapy and the fight against infectious disease. The central motivation behind the Molecule of the Month is to provide a user‐friendly introduction to this rich body of data, charting a path for users to get started with finding and exploring the many available structures. The Molecule of the Month and related materials are updated regularly at the education portal PDB‐101 (http://pdb101.rcsb.org/ ), offering an ongoing resource for molecular biology educators and students around the world.